Modifications Associated To O Vernutrition Evidenced During And After Physical E Fort, Havana - Lopez de Villavicencio Hernández, Claudia Ines; González Jardines, Mayppe; Cabrera Rojo, Ileana (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Obesity, "epidemic of the XXI century", affects the cardiovascular system, whose diseases are among the leading causes of morbimortality in most developed countries, as well as in some developing nations such as Cuba, where mortality rate of cardiovascular causes reached 228.2 every 100000 inhabitants in 2018. Classification: observational of prevalence, descriptive-correlational; transversal; and applied. Objective: To describe functional cardiac modifications associated with overnutrition and expressed during and after physical effort, Havana, Cuba. Population: 102 subjects who attended said laboratory with to have a periodical health follow-up from January 2017 to April 2018, of 30-70 years of age, without personal history of ischemic heart disease or contraindications to perform an Exercise Stress Test, and in whose attention the researchers participated. Method: Anamnesis, physical exam, bioimpedance and exercise stress test. The subjects were classified according to body fat percentage: groups N (normal), H (high) and V (very high). Results: 83 subjects completed the study, predominating women and subjects of 50-59 years of age. The most prevalent cardiovascular risk factors were overnutrition, sedentary lifestyle and hypertension. Functional capacity was diminished with the increase in body fat percentage (BFP). In subjects of group N there was no ST-segment deviation. 18 subjects presented arrhythmia during and after the exercise, among them 88,2% had a BFP higher than normal; the most frequent arrhythmias were sinus tachycardia and ventricular extrasystole. Conclusions: overnutrition is associated with functional cardiac modifications that imply an increase of cardiovascular risk, with decreased exercise tolerance and augmented incidence of ischemia and cardiac arrhythmias.